How Do Work-Life Balance and Work Environment Affect Employee Performance Through Job Satisfaction? - Aziz Imam Machmudi; Istiatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines how work-life balance, the work environment, and job satisfaction influence employee performance, emphasizing the mediating role of job satisfaction in these relationships at the Surakarta Medium Tax Service Office. A total of 117 employees participated, with data collected using a census sampling approach and questionnaires. The analysis was conducted using SmartPLS 3.0 software. The findings reveal that work-life balance, the work environment, and job satisfaction all significantly and positively impact employee performance. Furthermore, work-life balance and the work environment positively influence job satisfaction, which acts as a mediator connecting these factors to employee performance. The research highlights the critical role of improving work-life balance and fostering a supportive work environment to enhance job satisfaction and, consequently, employee performance.